Study of Needs for the Development of PBL-Based E-Modules to Improve Numeracy Literacy - Yuni Lestari; Nizlel Huda; Maison Maison (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study intends to ascertain whether e-modules based on problem-based learning (PBL) on numbers should be produced, when the current teaching resources are textbooks. For students, the supply of textbooks became a concern. The abstract issues in the textbook that pupils must solve continue to stump them. A descriptive approach is employed in the research method, which is qualitative. The information was gathered by giving questionnaires to 30 pupils who are familiar with the notion of numbers and by speaking with three math teachers at the school. The findings of this study (1) demonstrate that students require cutting-edge instructional materials in the form of e-modules. (2) To prevent students from getting easily bored while studying, PBL-based e-modules are not only delivered in written form; they can also be integrated to videos and animations.